2003
DOI: 10.1097/00001721-200302000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant activated factor VII combined with local measures in preventing bleeding from invasive dental procedures in patients with Glanzmann thrombasthenia

Abstract: Recombinant activated factor VII (rFVIIa), combined with local measures of fibrin glue and a celluloid splint, preventing bleeding from four invasive dental procedures is reported. A single dose of 180-200 micro g/kg was successfully used in three surgical removals of impacted teeth. Four doses of rFVIIa were required in another full mouth treatment of extraction, pulpotomy, filling and the stainless steel crowning of 13 teeth. The repeated dose of rFVIIa was given whenever the bleeding complication was visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…A literature review revealed equal or less dosing of rFVIIa in comparison to our patient [3,4,7,9,[11][12][13]. The frequency of dosing intervals and the total duration of treatment should be individually adjusted, depending on the type of surgery and according to patient's clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review revealed equal or less dosing of rFVIIa in comparison to our patient [3,4,7,9,[11][12][13]. The frequency of dosing intervals and the total duration of treatment should be individually adjusted, depending on the type of surgery and according to patient's clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant FVIIa has been shown to be effective in GT patients who are experiencing significant bleeding and who have either failed platelet transfusions, have platelet antibodies, or where it has been used to prevent platelet alloimmunization, and blood‐borne pathogen transmission. Many case reports have substantiated this success [69–74]. These are summarized in Table 2.…”
Section: Recombinant Fviia In Non‐haemophilia Bleeding In Childrenmentioning
confidence: 99%
“…For mild-to-moderate bleeding in GT, the following approach is generally practiced: i) Local pressure/use of fibrin glue/human thrombin or use of other products such as collagen matrix may be effective in cases of mild bleeding [19,20]. Gelatin sponges soaked with antifibrinolytics such as epsilon aminocaproic acid (EACA) or tranexamic acid is often used locally to stop superficial bleeding.…”
Section: Local Measuresmentioning
confidence: 99%